1994
DOI: 10.1083/jcb.126.2.391
|View full text |Cite
|
Sign up to set email alerts
|

ERM family members as molecular linkers between the cell surface glycoprotein CD44 and actin-based cytoskeletons.

Abstract: Abstract. The ERM family members, ezrin, radixin, and moesin, localizing just beneath the plasma membranes, are thought to be involved in the actin iliamerit/plasma membrane association. To identify the integral membrane protein directly associated with ERM family members, we performed immunoprecipitation studies using antimoesin mAb and cultured baby hamster kidney (BHK) cells metabolically labeled with [35S]methionine or surface-labeled with biotin. The results indicated that moesin is directly associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
509
2
11

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 737 publications
(546 citation statements)
references
References 62 publications
18
509
2
11
Order By: Relevance
“…This raises the question of whether these proteins might be interacting at the looped structure. It has been reported that ezrin links the cytoplasmic domain of CD44 to the actin cytoskeleton in baby hamster kidney cells and mouse L ®broblasts (Tsukita et al, 1994;Yonemura et al, 1998Yonemura et al, , 1999Legg and Isacke, 1998), but we do not know if this interaction occurs in FBR cells. None of our data allow us to conclude that Krp1 interacts with these proteins, but the presence of all of them at pseudopod tips upon transformation of 208F cells supports the hypothesis that AP-1 regulates the expression of these genes, and that they are recruited to a structure that is likely to allow transformed cells to become invasive (Guirguis et al, 1987;Hay, 1989;Lamb et al, 1997b;Liotta et al, 1991b;Nabi et al, 1999).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This raises the question of whether these proteins might be interacting at the looped structure. It has been reported that ezrin links the cytoplasmic domain of CD44 to the actin cytoskeleton in baby hamster kidney cells and mouse L ®broblasts (Tsukita et al, 1994;Yonemura et al, 1998Yonemura et al, , 1999Legg and Isacke, 1998), but we do not know if this interaction occurs in FBR cells. None of our data allow us to conclude that Krp1 interacts with these proteins, but the presence of all of them at pseudopod tips upon transformation of 208F cells supports the hypothesis that AP-1 regulates the expression of these genes, and that they are recruited to a structure that is likely to allow transformed cells to become invasive (Guirguis et al, 1987;Hay, 1989;Lamb et al, 1997b;Liotta et al, 1991b;Nabi et al, 1999).…”
Section: Discussionmentioning
confidence: 76%
“…CD44 antisense oligonucleotides caused a reduction in invasiveness in both of these cells. The expression of ezrin, which is a member of the ezrin/radixin/moesin (ERM) family and is thought to link CD44 to the cell's cytoskeleton, was also shown to be upregulated (Lamb et al, 1997b;Jooss and Muller, 1995;Tsukita et al, 1994). Ezrin is located at the tips of pseudopodia in FBR cells and EGF-treated 208F cells, and removal of it from pseudopodia using the micro-CALI technique resulted in retraction of pseudopodia, suggesting that ezrin has a role in pseudopod extension (Lamb et al, 1997b).…”
Section: Introductionmentioning
confidence: 99%
“…Merlin and the ERM proteins are members of the band 4.1 superfamily, all of which contain a FERM (4.1, ezrin, radixin, moesin) domain at their NH 2 -termini. Like the ERM proteins, merlin regulates actin cytoskeletal organization, cell architecture and motility (Algrain et al, 1993;Tsukita et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…CD44, the principal cell-surface receptor for hyaluronan (HA; Stamenkovic et al, 1989;Aruffo et al, 1990), is one of the transmembrane proteins that interact with ERM proteins and merlin (Tsukita et al, 1994;Hirao et al, 1996;Sainio et al, 1997;Tsukita and Yonemura, 1997;Morrison et al, 2001). There are numerous isoforms of CD44, the most commonly expressed isoform is the standard form of CD44 (CD44s) that lacks variant exon products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation